2021
DOI: 10.1186/s13098-021-00736-2
|View full text |Cite
|
Sign up to set email alerts
|

Klotho and SIRT1 changes from pre-diabetes to diabetes and pre-hypertension to hypertension

Abstract: Background Hypertension and diabetes are among the most important risk factors of cardiovascular diseases. Klotho and SIRT1 are known as anti-aging factors with beneficial effects on cardiovascular system. In this study we investigated the serum Klotho and SIRT1 levels in pre-diabetic and pre-hypertensive individuals and then in diabetic and hypertensive patients to see their relationship with these diseases. Method 229 individuals divided into six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Taken together, the discrepancies among previous publications can be largely attributed to the dynamic changes in Klotho expression at different stages of diabetes. This explanation was consistent with the findings from another study that the serum levels of Klotho increased at the onset of diabetes as a potential compensatory mechanism in response to high glucose stimulation, while their levels recovered as diabetes progressed ( 41 ). More importantly, considering that kidneys act as a major source of endogenous Klotho and the presence of elevated Klotho levels is highly related to preserved renal function ( 42 ), we may speculate that serum Klotho concentration serves as a biomarker of the number of functional nephrons and therefore reflects the degree of renal impairment induced by high glucose.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, the discrepancies among previous publications can be largely attributed to the dynamic changes in Klotho expression at different stages of diabetes. This explanation was consistent with the findings from another study that the serum levels of Klotho increased at the onset of diabetes as a potential compensatory mechanism in response to high glucose stimulation, while their levels recovered as diabetes progressed ( 41 ). More importantly, considering that kidneys act as a major source of endogenous Klotho and the presence of elevated Klotho levels is highly related to preserved renal function ( 42 ), we may speculate that serum Klotho concentration serves as a biomarker of the number of functional nephrons and therefore reflects the degree of renal impairment induced by high glucose.…”
Section: Discussionsupporting
confidence: 92%
“…CEACAM1 [340], ACSL1 [341], TLR4 [342], ABCA1 [343], TLR5 [344], CYP2D6 [345], JAK2 [346], NOTCH2 [347], DDX3X [348], NCOA4 [349], EGR1 [350], IQGAP2 [351], GCLC (glutamate-cysteine ligase catalytic subunit) [352], VEGFA (vascular endothelial growth factor A) [353], ITGB1 [354], LDLR (low density lipoprotein receptor) [355], TLR6 [316], SIRT1 [356], FGL2 [357], TET2 [358], PHF2 [328], VEGFB (vascular endothelial growth factor B) [359], SELENOM (selenoprotein M) [360], TRPM4 [361], OLFM2 [362] and ATAD3A [363] are thought to be involved in non-alcoholic fatty liver disease. Altered expression of ATOH8 [364], STAT1 [365], ARG1 [366], TLR4 [367], VNN1 [368], ABCA1 [369], IFIH1 [370], PTGS2 [371], F2RL1 [289], CYP2D6 [372], PDK4 [373], RNF213 [374], JAK2 [375], NOTCH2 [376], PDGFC (platelet derived growth factor C) [377], TLR2 [378], CYP1B1 [379], IL1RN [380], GCH1 [381], EGR1 [382], HIF1A [383], PLA2G7 [384], CCR2 [385], GAB1 [386], VEGFA (vascular endothelial growth factor A) [387], OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) [388], OXR1 [389], IRF9 [390], FMR1 [391], LDLR (low density lipoprotein receptor) [392], SIRT1 [393], NOD2 [394], ATP13A3 [395], VCAN (versican) [396], FGL2 [397], TET2 [398], KDM6A [399], KLHL2 [400], CAVIN1 [401], TNFRSF4 [402], PF4 [403], VEGFB (vascular endothelial growth factor B) [330], CCR7 [404], PRDX2 [405], HSPB1 [406], TCF4 […”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that EGR1 [350] and SIRT1 [356] are altered expressed in non-alcoholic fatty liver disease. Previous studies have shown that EGR1 [382], SIRT1 [393], STAT1 [365], HIF1A [383] and IRF9 [390] might influence the prognosis in hypertension. EGR1 [449], SIRT1 [458] and STAT1 [435] are a genes which plays a role in diagnosis of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The role of epigenetic regulators in tumor targeted therapy has been of critical interest [30]. The anti-aging gene sirtuin 1 (SIRT1) has been reported to be associated with LUAD and non-small cell lung cancer and high protein level of SIRT1 has been shown to indicate poor prognosis of lung cancer patients [18,[31][32][33]. SIRT1 is involved with transcription dysregulation including deacetylation of transcription factors such as p53 and DNA methylation [34][35][36].…”
Section: Discussionmentioning
confidence: 99%